(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
This essay is a ponderation about the spiritual crisis that the Western world is experiencing, and its reflection in architecture. The analysis is basically based on the Anthropological Structures of the Imaginary proposed by the anthropologist Gilbert Durand, to demonstrate how architecture reflects the patterns of an exacerbated diurnal regime, where the human vital experience, the symbolism and poetics of space, and the search for meaning and depth, are transgressed by a desire of flight, detachment, immediacy, artificiality, exposure, appearance and superficiality that disengage and separate individuals and societies.